Parameterized Random Complexity - Montoya, Juan Andrés; Müller, Moritz (Theory of computing systems, 2013)
The classes W[P] and W[1] are parameterized analogues of NP in that they can be characterized by machines with restricted existential nondeterminism. These machine characterizations give rise to two natural notions of parameterized randomized algorithms that we call W[P]-randomization and W[1]-randomization. This paper develops the corresponding theory.